2002
DOI: 10.1897/1551-5028(2002)021<0752:eoctot>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Contact Time on the Sequestration and Bioavailability of Different Classes of Hydrophobic Organic Chemicals to Benthic Oligochaetes (Tubificidae)

Abstract: Differences in bioavailability of hydrophobic organic compounds (HOC) to benthic deposit feeders have been related to differences in sediment-HOC contact time and sequestration (formation of slowly desorbing fractions) status. As a consequence, it was postulated that contact time and/or sequestration should be incorporated into risk assessment. In the present study, we investigated the effect of contact time on the bioavailability and sequestration of different classes of HOC. For this purpose, we simultaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 26 publications
3
45
0
Order By: Relevance
“…These regressions were not quite as good as that found for PAH only (r 2 ϭ 0.76 [1]) or for PAH and chlorobenzenes (r 2 ϭ 0.77, [2]). If we remove the PCBs from the regressions, then the linear regressions for BSAF versus F rapid for PAH only would have r 2 values for 54 and 64% for L. variegatus and Diporeia, respectively, where our regression is across seven sediments and that of Kraaij et al [1,2], which is for a single sediment. Thus, these appear to be comparable considering the potential additional variability that would result from accumulation across seven sediments.…”
Section: Discussionmentioning
confidence: 56%
“…These regressions were not quite as good as that found for PAH only (r 2 ϭ 0.76 [1]) or for PAH and chlorobenzenes (r 2 ϭ 0.77, [2]). If we remove the PCBs from the regressions, then the linear regressions for BSAF versus F rapid for PAH only would have r 2 values for 54 and 64% for L. variegatus and Diporeia, respectively, where our regression is across seven sediments and that of Kraaij et al [1,2], which is for a single sediment. Thus, these appear to be comparable considering the potential additional variability that would result from accumulation across seven sediments.…”
Section: Discussionmentioning
confidence: 56%
“…The sediments were spiked in equimolar concentrations at 360 nmol/kg with four radiolabeled HOCs in two treatment groups including one PAH and one polychlorinated biphenyl congener in each treatment. The four radiolabeled HOCs were 3 H-pyrene (PY, specific activity 25.2 Ci/mmole), 14 C-3,3Ј,4,4Јtetrachlorobiphenyl (TCBP, specific activity 12.5 mCi/mmole), 3 H-benzo[a]pyrene (BaP, specific activity 50.0 Ci/mmole), and 14 C-2,2Ј,4,4Ј,5,5Ј-hexachlorobiphenyl ([HCBP], specific activity 12.6 mCi/mmole). Nonlabeled PY (purity Ͼ99%) and BaP (purity Ͼ98%) obtained from Aldrich (Milwaukee, WI, USA) were added with the radiolabeled compounds to limit the amount of radioactivity required.…”
Section: Sediment Spikingmentioning
confidence: 99%
“…In an analogous manner, bioaccumulation investigations have also focused on the kinetics of HOC bioaccumulation, with the thought that HOC accumulation is a function of rate limitations ensuing from intra-aggregate HOC desorption [11][12][13]. Recent studies in this area suggest that HOCs are sorbed to ''rapid desorbing'' and ''slower desorbing'' pools of organic matter in sediment aggregates [13][14][15][16]. This approach has indicated that the most rapidly desorbing pool of an HOC from a particle aggregate may be the most relevant with respect to HOC bioaccumulation [12][13][14]17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aquatic ecotoxicology and risk assessment traditionally have relied on quantifying the contaminant concentrations in water and sediment that elicit toxic effects. However, there are many important factors, such as bioavailability, uptake kinetics, habitat, and feeding behavior, which determine to what extent the toxicants present in the system will reach the target sites in organisms (e.g., [1][2][3][4][5][6][7][8]). Measuring the internal concentration in organisms themselves automatically takes into account many of the factors that impact the correlation between external concentration and toxicity and, therefore, is a better indicator of the concentrations at target sites than external concentrations [6,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%